Learning Reading Beam No Tation Using Pianika Musical Instrumen For College Students Semester 1 Music Educations UNWIRA Kupang - Yunita Indriani Banfanu; Margareta Sofyana Irma Kaet; Flora Ceunfin (Edumaspul: Jurnal Pendidikan, 2025)
This study examines learning to read sheet music using the pianica instrument for first semester students of the Music Education Study Program, UNWIRA Kupang, who generally do not have this ability well. The main objectives of this study are to: 1) Determine the process and results of learning to read sheet music. 2) Analyze the difficulties experienced by students in this learning and how to overcome them. In this study, ten meetings were conducted, which included the delivery of materials, etude practice exercises, and practice reading the song "Ampar-Ampar Pisang". The results showed that all students succeeded in mastering the components of sheet music, including form, note value, staff, and key signature. The difficulties faced by students included note value, beats, staff, and key signature, which were overcome through repeated practice and imitation. The assessment showed an increase in competence from a score of 30 at the second meeting to 90 at the ninth meeting. The study used a qualitative approach with a field action method, as well as data collection techniques through observation, interviews, and documentation. The research subjects were six students who were selected based on certain criteria.